Impact of Yoga Practice on Lipid Profile and Insulin Resistance in Overweight and Obese Individuals – A Pilot Study - Abhijeet Shelke; Ramesh Kawade; Subhradeep Bhattacharya; Vishal Sarkar; Neevhashiny Selvaraj (Journal of the Scientific Society)
Objective: This pilot study was designed to analyze the effect of yoga on cardiometabolic functions in overweight and obese individuals. Methods: A prospective interventional study was carried out at a tertiary care center in India for 8 weeks. A total of 50 participants were enrolled in the study of which only 29 were regular in yoga intervention. Participants between 25 and 60 years of age, overweight and obese individuals with body mass index ≥25 kg/m2, and those willing to adhere with all the instructions including avoidance of caffeine throughout the study period were included in the study. Baseline demographic details, anthropometric measurements, and biochemical measurements were recorded before and after yoga intervention. Results: After 8 weeks of daily yoga intervention, data of 29 regular attendees were analyzed. The mean age was 44.2 ± 12.3 years and females (72.4%) were predominant than males (27.6%). Homeostasis model assessment-estimated insulin resistance (P < 0.001), fasting blood glucose (P < 0.001), fasting insulin (P < 0.006), quantitative insulin sensitivity check index (P < 0.001), and glycosylated hemoglobin (P = 0.001) were statistically significant, before and after yoga intervention. Furthermore, a statistically significant difference was observed in lipid profiles such as total cholesterol (P < 0.001), low-density lipoprotein (LDL) (P < 0.001), very LDL (P < 0.005), and triglycerides (P < 0.001) before and after yoga intervention. Conclusion: Yoga intervention demonstrated an improved lipid profile and glucose intolerance which subsequently advances cardiometabolic health. However, findings are limited by small sample size and pilot study.